The X Factor in Understanding Listening Comprehension Skill - Bustami Usman; Chairina Nasir; Tiya Akmalia (Universitas Syiah Kuala, 2019)
This research was aimed to find out factors affecting students’ challenges in listening comprehension as perceived by students at SMAN 1 Calang. This is a descriptive qualitative study. The samples of this research were selected by using purposive sampling. There were 75 eleventh-grade students who participated in this research. Questionnaire and interview were designed as research instruments. The questionnaire consisted of 30 items grouped into five categories, namely students’ listening comprehension challenges related to factors attributed to the content and linguistics features of the listening text, factors attributed to the speaker, factors attributed to the listener, and factors attributed to the physical setting. Moreover, the interview consisted of three questions asking students’ opinion about listening comprehension, challenges they faced in listening comprehension activity, and factors that caused those challenges. The result indicates listening texts, speaker, listener, and physical setting were the main sources of students’ listening comprehension challenges. The dominant factor affecting students’ challenges in listening comprehension was the physical setting such as the noise from environmental surroundings, with the percentage of 89.6%.